Non-discrimination against handicapped in the EU and Turkey with special emphasis on education and training - Türemen, M. Ebru Dayanç (My University, 2006)
Bu çalışmada, AB ülkeleri ve Türkiye’deki engelli bireylerin eğitim, istihdam ve ayrımcılık alanlarındaki durumlarının saptanması ve karşılaştırılmasını amaçlanmıştır. Avrupa Birliği ülkelerinde ayırımcılığın en yoğun hissedildiği sosyal politika alanlarından istihdam ve eğitim sosyal katılımın ve refahın önemli unsurları olarak karşımıza çıkmaktadır. Özel eğitimin önemi bunun özürlülük politikaları ve projelerinin oluşturulmasına temel oluşturmasından kaynaklanmaktadır. Engellilerin sosyal hayata ve bilhassa iş gücüne katılımları, onların eğitimlerine karşı duyarlı olan konulardır. Engellilik ve ayırımcılık kavramları ile bunların dayanağı olan sosyal politikalar üzerindeki literatür araştırmaları Avrupa Birliği, Amerika Birleşik Devletleri ve Türkiye’de bu konuda yoğun çalışmaların yapıldığını göstermektedir. Avrupa Birliği ülkeleri arasında İngiltere engellilere yönelik ayırımcılık karşıtlığında yerleşik mevzuata sahip tek ülke olarak belirlenmiştir. Fransa ise sosyal göstergelere bakıldığında geniş çaplı engelli ayırımcılığına yol açan kurumsallığın fazla olduğu ülke olarak görülmektedir. Avrupa Birliği’nin sektörel parçaların bir araya toplanması ile 2010 yılında Engelli Eylem Planını tamamlayarak bir Engellilik Yasası çıkarabileceği sonucuna varılmıştır. Yaşlanan nüfusu göz önüne alındığında, Avrupa Birliği engellileri iş gücüne katarak sürdürülebilir refahını geliştirmek istemektedir. AB ülkeleri yanı sıra, sosyal göstergelere bakıldığında, Türkiye’nin de istihdam ve eğitim alanlarında mevzuat uygulamasından kaynaklanan ayırımcılık sorunları bulunduğu ortaya çıkmaktadır. Türkiye hali hazırda engellilerin eğitim ve istihdam düzeylerini yükseltecek kapsamlı projeler üzerinde çalışmaktadır. Avrupa Birliği müktesebatıyla ilgili konularda uyumlaştırma Türkiye’nin öncelikleri arasındadır.

The study aims to determine and compare the existing situation of the people with disabilities in the fields of education, employment and discrimination in the European Union countries and Turkey. Since the social domains employment and education are the key elements for social inclusion and social welfare for the sake of elimination of discrimination, they are the social policy areas in which the effect of discriminative attitude is felt heavily in the EU countries. So, they become primary research areas. The importance of education of the disabled or “special education” is that it acts as a foundation stone in the development of disability policies and projects. Participation of people with disabilities into social life and especially to labour force is sensitive to their education. The researches on disability and discrimination and related social policies in these fields indicate that there are promising studies realised in the EU, USA and Turkey. The UK appears to be the only European country that has a well organised legislation on disability anti-discrimination. On the other hand, when the social indicators are considered, France has been found as the country with weighted institutionalism which leads to disability discrimination to a certain extent. It could be concluded that the EU seems to declare a Disability Law by 2010 bringing its sectoral parts into an inclusive whole following its Disability Action Plan. The EU also needs to improve its sustainable prosperity by including the people with disabilities in its labour force when the aging population of the EU is considered. Besides the EU countries, it is pointed out by social indicators that there are discrimination problems in employment and education fields stemming from the implementation of the legislation in Turkey as well. Turkey is currently working on comprehensive projects to increase the education and employment level of the people with disabilities. Harmonisation with the EU acquis in the related fields is among the priorities of Turkey.
Keywords: Avrupa Birliği_Eğitim_Türkiye; Avrupa Birliği_İstihdam_Türkiye; Fiziksel Özürlüler_Eğitim